Effects of microwave and induction heating on the mechanical and self-healing characteristics of the asphalt mixtures containing waste metal - Yalcin, Erkut (Elsevier Sci Ltd, 2021)
In this study, the effects of microwave and induction heating on the self-healing of asphalt mixture samples with waste metals were investigated. Furthermore, the effects of waste metals, which were used in place of aggregates, on the mechanical properties of asphalt mixtures were examined. With this purpose, two different waste metals (hot mill scale (HMS) and cold mill scale (CMS)) in two different ratios (within the range of 2.36-0.6 mm, 50% and 100%) were used instead of limestone aggregate, and the prismatic and cylindrical asphalt test samples were prepared. The induction and microwave heating methods were used to determine the self-healing characteristics. In both methods, the samples were subjected to the heating process in four different durations (40, 60, 80, and 100 s). Five healing cycles were carried out for each asphalt sample to measure the efficiency of the healing process. Prior to the application of the healing processes, it was observed that the asphalt mixtures with HMS had lower amounts of air voids compared to the mixtures with CMS. As the ratio of the waste metal in the asphalt mixture increased, the stiffness modulus and fatigue life of the mixtures decreased. In the analyses, it was determined that the microwave heating method yielded better self-healing characteristics in asphalts pavements compared to the induction heating method. Furthermore, each healing cycle conducted with asphalt mixtures reduced the healing performance further. Despite the improvements in self-healing, the microwave heating resulted in degradations in the mechanical properties of the asphalt mixtures. It was concluded that the healing level in asphalt mixtures, which was tested using the microwave and induction heating methods, depended on the healing duration and the type and content of the waste metal used. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Waste metal; Induction heating; Microwave heating; Self-healing; Mechanical performance